The occurrence of humpback whales across the Hawaiian archipelago revealed by fixed and mobile acoustic monitoring - Lammers, Marc O.; Goodwin, Beth; Kügler, Anke; Zang, Eden J.; Harvey, Matt; Margolina, Tetyana; Martinez, Jonathan A.; Merkens, Karlina; Hatch, Leila T. (Frontiers in Marine Science, 2023)
The occurrence of humpback whales (Megaptera novaeangliae) across the 2600 km of Hawaiian archipelago, which include the remote atolls, banks, and seamounts of Papahānaumokuākea Marine National Monument (PMNM), remains poorly understood. Previous surveys for humpback whales beyond the main Hawaiian Islands have been scarce due to limited access and the challenging winter conditions typically found in PMNM when whales are present. To overcome these limitations, a combination of moored acoustic recorders and a Wave Glider autonomous surface vehicle were used to acoustically monitor eight locations and survey approximately 1500 km of the Hawaiian archipelago for the occurrence of humpback whale song during the 2019-2020 breeding season. Relative song prevalence was established using a machine learning tool and by quantifying the level of song chorusing. A generalized additive model framework was applied to understand the associations between habitat variables and humpback whale song occurrence, and sound propagation modeling was performed to examine whether acoustic propagation influenced observed patterns. Whale song was recorded at all monitored and surveyed locations across the archipelago, albeit in varying amounts. Among the locations monitored with moored recorders, the highest and most sustained seasonal chorusing levels were measured off Maui followed by French Frigate Shoals (Kānemilohai), Hawaii Island, Middle Bank, Oahu, Kauai, Gardner Pinnacles (Pūhāhonu) and Pearl and Hermes Reef (Holoikauaua), respectively. The Wave Glider mission to PMNM revealed that song prevalence was highest at Middle Bank and gradually decreased further to the northwest, reaching a minimum at Gardner Pinnacles (Pūhāhonu). However, song occurrence increased again at Raita Bank, remaining high between Raita Bank and the Northampton Seamounts. The results reveal that nearly the entire Hawaiian archipelago is exploited by humpback whales during the winter and early spring months. Moreover, song occurrence patterns suggest that there may be more structure in the distribution of whales in PMNM than previously known and raises questions about whether multiple subpopulations occur across the archipelago.